Plant–plant interactions vary greatly along a flooding gradient in a dam-induced riparian habitat - Ying, Liu; Yanfeng, Wang; Wenzhou, Wu; Zhi, Ding; Maohua, Ma; Ping, Huang; Shengjun, Wu; Yanjing, Lou (Frontiers in Plant Science, 2023)
perennial clonal plants to periodic flooding stress, whereas belowground resource (water and nutrients) was probably the dominant factor for perennial clonal plants.Our study will help to further understand the environmental responses of plant-plant relationships and its regulatory mechanism, and the succession of riparian plant communities under extreme environmental changes, providing basic theoretical basis and data support for the ecological restoration and management of riparian wetland vegetation.